A dreaded procedural complication during endoscopic retrograde cholangiopancreatography - Ramdas, E K; Pallivalappil, Bhargavan; Jithin, N T; Muaralidharan, Rajesh; Sarpamale, Avinash; Dani, Shafri (Indian Journal of Case Reports, 2020)
Endoscopic retrograde cholangiopancreatography (ERCP) procedure has gained popularity and has become the method of choice for diagnostic and therapeutic modalities. But there is a concern about albeit concerns about the dreaded serious complications that can be a threat to the life of subjects. We, herein, report a case of air embolism. A 30-year-old lactating woman presented with nausea, vomiting, and epigastric pain for 2 weeks with deranged liver function tests. Computed tomography abdomen was suggestive of gallbladder calculus with the prominent common bile duct. She was electively posted for the ERCP procedure. During the course of procedure, untoward complication was encountered, and with transthoracic echocardiography and fluoroscopy, diagnosis of air embolism was more or less confirmed. In spite of our tremendous resuscitative maneuvers, the condition deteriorated and later succumbed to death.